Phylogeny and classification of Callimorphini (Lepidoptera: Arctiidae: Arctiinae) - Dacosta, M. A.; Weller, S. J. (Zootaxa, 2005)
A preliminary phylogeny for the Callimorphini and related tribes was constructed based on adult morphology. The data matrix, consisting of 91 taxa and 116 characters (299 states), was analyzed using maximium parsimony. To test the monophyly of the Callimorphini s.s. and determine the placement of the Euchaetes group, 49 ingroup species and 42 outgroup species were included. Callimorphini was represented by 23 species (11 genera), and the Euchaetes group was represented by 26 species (6 genera). Outgroup taxa include both root genera from the Arctiini (10 genera, 12 species) and representative genera from related tribes as “internal outgroups.” Internal outgroups included representatives from Phaegopterini (6 genera, 9 species), Nyctemerini (1 genus, 9 species), and Pericopini (7 genera, 12 species). The data matrix included both nongenitalic and genitalic characters as follows: 7 head (17 states), 5 leg (10 states), 22 wing (57 states), 12 thoracic (29 states), 39 male abdominal and genitalic characters (95 states) and 31 female abdominal and genitalia (91 states). Of these, 36 were multistate and were treated as unordered. Heuristic searches with 20, 100, and 1000 random–taxon additions were performed to sample multiple tree islands. This study also assessed the utility of adult genitalic character systems for confident resolution of older divergences. The resulting cladistic analysis demonstrated that phylogenetic relationships among closely related genera were recovered; however, genitalic characters do not fully replace information from immature stages. Relationships among major clades remained poorly supported as determined by taxon and character jackknifes. Based on these results, a revised concept for Callimorphini is proposed based on well–supported relationships. A checklist of callimorphine genera also is provided. The Old World genus Nyctemera is placed in the Pericopini rev. placement and Euchaetes and allied genera are placed in the Phaegopterini rev. placement.KEY WORDS: Arctiidae, Callimorphini, phylogenyCallimorphini (Lepidoptera: Arctiidae: Arctiinae), like many tiger moths, are cosmopolitan in distribution and most diverse in the tropics. Adults frequently are brightly colored with orange, pink, yellow, and red scales on the wings and abdomen (Ferguson 1985, Holloway et al. 2001). Some members of the Callimorphini, a small tribe of approximately 108 species, resemble butterflies in that they are diurnal (e.g., Utetheisa Hübner) or have large wings and “slender” bodies characteristic of butterflies (e.g., Haploa Hübner, Callimorpha Latreille) (Figs. 1, 2). Callimorphini, and tiger moths more generally, have captured the attention of scientists because of their coloration and their intriguing biology. In general, arctiid larvae and adults defend themselves from predators with biogenic amines, often in combination with host–plant derived chemicals such as pyrrolizidine alkaloids (PAs), cardiac glycosides (CGs), or sesquiterpenes (reviews: Weller et al. 1999; Conner & Weller 2004). These compounds can be found in all life stages in several species. Callimorphini is pivotal for understanding the evolutionary transitions among the different defense strategies within the subfamily Arctiinae (Fig. 3; Weller et al. 1999). Most callimorphines use pyrrolizidine